Wellens Syndrome in a patient with a history of hypertension and chronic obstructive pulmonary disease: a case report - Ririn Ramli; Makhyan Jibril Al Farabi; Bestya Presidiana; Ricardo Adrian Nugraha; Pandit Bagus Tri Saputra; Yudi Her Oktaviono (Journal of the Pakistan Medical Association, 2024)
Wellens syndrome, an ST Elevation Myocardial Infarction (STEMI) equivalent, is also known as T-wave left anterior descending (LAD) coronary artery disease. Wellens syndrome is characterized by a unique electrocardiogram (ECG) pattern that suggests a significant stenosis in the left anterior descending coronary artery that warrants immediate intervention. Hereby, we present a case report of Wellens syndrome in a patient with a history of hypertension and chronic obstructive pulmonary disease (COPD) that may be potentially mistaken for pseudo- Wellens syndrome because the ECG pattern mimics left ventricular strain pattern (LVSP) in left ventricular hypertrophy (LVH). Thus, cautious examination of recent chest pain and ECG is important to differentiate Wellens syndrome and LVSP in patients with hypertension and COPD to perform early detection and aggressive intervention since they may help to lessen the adverse results. Keywords: Coronary Artery Disease, Myocardial, Electrocardiography, Chest Pain, Hypertrophy, Arrhythmias, Cardiac